ICE-LAPSE image dataset - Simone Marini; Federico Bonofiglio; Lorenzo Paolo Corgnati; Andrea Bordone; Stefano Schiaparelli; Andrea Peirano (Zenodo, 2022)
######################################################## Image dataset acquired within the project "ICE-LAPSE: Analysis of Antarctic benthos dynamics by using non-destructive monitoring devices and permanent stations'', PNRA 2013/AZ1.16, funded by the Italian National Antarctic Program. The dataset is in support of the publication entitled: Long-term Automated Visual Monitoring of Antarctic Benthic Fauna Simone Marini 1,2∗ , Federico Bonofiglio 1 , Lorenzo P. Corgnati 1 , Andrea Bordone 3, Stefano Schiaparelli 4 , Andrea Peirano 3 1 National Research Council of Italy (CNR), Institute of Marine Sciences, La Spezia, 19132, Italy, 2 Stazione Zoologica Anton Dohrn, Naples, 80121, Italy 3 ENEA-Marine Environment Research Centre, La Spezia, 19132, Italy 4 DISTAV, Università di Genova, Genova, 16132, Italy ∗E-mail: simone.marini@sp.ismar.cnr.it. HOW TO CITE: Marini, S., Bonofiglio, F., Corgnati, L. P., Bordone, A., Schiaparelli, S., & Peirano, A. (2022). Long-term automated visual monitoring of Antarctic benthic fauna. Methods in Ecology and Evolution , 00, 1– 19. https://doi.org/10.1111/2041-210X.13898 ######################################################## The dataset consists of four .tgz archives, structured as in the following: - Raw_Images contains the images in CR2 format - JPG_Images contains the images in JPG format - 640x427_Images contains the images in JPG format, with resolution 640x427 Pixels - ICE-LAPSE_Tags contains - the textual_Tags folder, - the Tagged_Images folder, - the SpeciesColorLabel image representing the legend for the tagged images contained in the Tagged_Images folder - the SpeciesDistribution.csv spreadsheet listing the species for each image